Implementasi E-Bussines dan Dampaknya Terhadap Pertumbuhan UMKM - Rahmawati, Feti; Sihombing, Veronika Dinar Romauli; Fauziah, Fauziah; Astuti, Tri; Redjeki, Finny (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The development of information technology has changed the business landscape globally, including in Indonesia. E-business is one of the main strategies for Micro, Small and Medium Enterprises (MSMEs) to increase competitiveness in the digital era. This research aims to analyze the implementation of e-business in MSMEs in Indonesia and its impact on business growth. This research uses a qualitative method with a case study approach on five MSMEs that have adopted e-business. The research results show that e-business contributes significantly to increasing operational efficiency, market expansion and revenue growth. However, challenges such as lack of digital literacy and technological infrastructure are still obstacles. The conclusion of this research confirms that government support and increasing the digital capacity of MSME players are key factors in the success of e-business implementation